Palladium(II) Complex of the 5-Hydroxypyridine-2-carbaldehyde N(4)-ethylthiosemicarbazone: Synthesis and Characterization - Yadav, Paras Nath; Bhattrai, Laxman; Mehta, Pramod K. (Journal of Nepal Chemical Society, 2013)
The novel complex of 5-hydroxypyridine-2-carbaldehyde N(4)-ethylthiosemicarbazone (HPyEt) with plalladium(II) have been prepared and characterized by elemental analysis, IR, 1H-NMR, UV-visible spectroscopy and mass spectrometry (FAB). Coordination of the anionic thiosemicarbazone ligand is via the pyridyl nitrogen, imine nitrogen and thiolato sulfur atoms and the fourth coordination site being occupied by chloride ion in square planar geometry. DOI: http://dx.doi.org/10.3126/jncs.v28i0.8040 Journal of Nepal Chemical Society Vol.28, 2011 Page 34-41 Uploaded date: March 6, 2013